2020
DOI: 10.3389/fmed.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Stroma Related Genes in Breast Cancer: A Comprehensive Analysis of Tumor Microenvironment Based on the Cancer Genome Atlas (TCGA) Database

Abstract: Background: Tumor microenvironment is essential for breast cancer progression and metastasis. Our study sets out to examine the genes affecting stromal and immune infiltration in breast cancer progression and prognosis. Materials and Methods: This work provides an approach for quantifying stromal and immune scores by using ESTIMATE algorithm based on gene expression matrix of breast cancer patients in TCGA database. We found differentially expressed genes (DEGs) through limma R package. Functional enrichments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 84 publications
(76 reference statements)
2
43
1
Order By: Relevance
“…Its high expression was observed to be associated with favorable overall survival of patients with oral cancers ( Hirohata et al, 2018 ). P2RY13 encodes a protein belongs to the family of G-protein coupled receptors, moreover, its high expression demonstrated significantly higher overall survival rates in patients with breast cancer ( Xu et al, 2020 ) and lung adenocarcinoma ( Fan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its high expression was observed to be associated with favorable overall survival of patients with oral cancers ( Hirohata et al, 2018 ). P2RY13 encodes a protein belongs to the family of G-protein coupled receptors, moreover, its high expression demonstrated significantly higher overall survival rates in patients with breast cancer ( Xu et al, 2020 ) and lung adenocarcinoma ( Fan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we observed the statistically significant difference between two age groups with regard to patient outcomes in the IntCl1, possibly owing to immunerelated genes. Indeed, many previous studies were of interest to the interaction between the immune system and age factor in BRCA (Fuentes et al, 2017;Li et al, 2020;Xu et al, 2020). Especially, Li et al (2020) indicated that there was a positive correlation of aging with i) the lower median immune/stromal scores and ii) the lower OS of BRCA patients.…”
Section: Prognostic Factor Identificationmentioning
confidence: 99%
“…At present, approximately 25 malignant tumor types have been evaluated by ESTIMATE using expression data across different platforms (12). Furthermore, stromal or immune scores have been analyzed in clinical data to predict tumor progression (13), treatment (14), and prognosis (15). However, these investigations involve only one cancer and therefore cannot compare the differences and explore common characteristics among many kinds of cancers.…”
Section: Introductionmentioning
confidence: 99%